LITERATURE REVIEW: LAW ENFORCEMENT'S ROLE IN ACCELERATING TAXPAYER COMPLIENCE ESCALATION - Sari, Vanisa Ratna; Okfitasari, Antin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to find out how far the effectiveness of law enforcement in Indonesia can increase taxpayer compliance so that it can increase state revenues in the field of taxation, and find out more about the law enforcement process that occurs in Indonesia. The existence of consistent tax law enforcement is one way for taxpayers to comply with tax regulations so that it can influence the state's income from the tax sector. The type of research used by researchers in this research is descriptive research. This type of descriptive research is used to describe the relationship between taxpayer compliance, tax audits, and tax collection on tax revenues in Indonesia. The method used in the data collection stage is literature study. Literature studies are carried out by collecting and analyzing data from various relevant literature sources such as scientific journals, books, research reports and tax regulations. The conclusion from this research is that taxpayer compliance and tax audits have a positive effect on tax revenues. Keywords: Law Enforcement, Tax Audit, Tax Revenue, Tax Payer